COLLOCATIONS OF DISCOURSE MARKER I MEAN IN BRITISH NATIONAL CORPUS - Mutiara, Rika; Aini, Safi (Kajian Linguistik dan Sastra, 2020)
The study aims at exploring functions, meaning, and pragmatic effects of co-occurrences of I mean and conjunctions in British National Corpus. The study applied some principles of a corpus study. I mean collocates with 5 conjunctions namely because, but, coz, when, and if. The collocations function to make the ideas clear in order to make the hearers understand them easily and avoid misunderstanding. They, moreover, are used when the speakers give corrections. They are uttered to emphasize arguments and give information as detailed as possible. These collocations in discourse make the hearers aware of information given and finally they pay special attention to the message.